Exploration of the antioxidant and antimicrobial capacity of two sunflower protein concentrate films with naturally present phenolic compounds - Salgado, Pablo Rodrigo (2012)
The aim of this study was to assess the potential activation of sunflower protein films with antioxidant and antimicrobial properties conferred by the phenolic compounds of sunflower seeds, which remain associated to the proteins used as starting material for film preparation. Two sunflower protein concentrates obtained from the residual pellet of oil industry were used, which had different content of phenolic compounds, mainly chlorogenic and caffeic acids. The film-forming dispersions and the films obtained were analyzed regarding their antioxidant properties (using ABTS, FRAP and PCL assays) and their antimicrobial properties (by agar disk diffusion tests). Phenolic compounds conferred important antioxidant properties to both dispersions and films, this activity being dependent on their content and their free or protein-bound nature. These compounds, however, did not confer their characteristic antimicrobial properties reported in previous studies, possibly due to their interaction with proteins and the pH of the film-dispersions. Since the antioxidant activity of phenolic compounds was preserved during the protein concentration process (inherent to the film formation), these protein matrices may be considered useful for protecting these bioactive compounds. © 2012 Elsevier Ltd.